Treating Drill Cuttings Waste with Oil Contamination by Microwave Treatment then by Earthworms Technique - Khdair, Ahmed Ameen; A. Al-Haleem, Ayad (Iraqi Journal of Chemical and Petroleum Engineering, 2021)
In this research paper, two techniques were used to treat the drill cuttings resulting from the oil-based drilling fluid. The drill cuttings were taken from the southern Rumaila fields which prepared for testing and fixed with 100 gm per sample and contaminated with two types of crude oil, one from Rumaila oilfields with Sp.gr of 0.882 and the other from the eastern Baghdad oilfield with Sp.gr of 0.924 besides contamination levels of 10% ​​and 15% w/w in mass. Samples were treated first with microwave with a power applied of 540 & 180 watts as well as a time of 50 minutes. It was found that the results reached below 1% w/w in mass, except for two samples they reached below 1.5% w/w in mass. Then, the sample of 1.41% w/w in mass, which has the highest contamination level after microwave treatment, was treated on three groups of earthworms. After the appropriate conditions, samples were prepared for treating by earthworms and for an incubation period of 21 days, the results highlighted the effectiveness of the succession process by reaching concentrations below 0.92%, 0.65%, and 0.42% w/w in mass.